Project-based learning in analytical geometry: Problem-solving and representational reasoning - Usep Kosasih (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2026)
Developing meaningful problem-solving approaches remains a central challenge in undergraduate Analytical Geometry courses. This study explores students’ learning experiences and approaches to problem-solving following the implementation of Project-Based Learning (PjBL) in an Analytical Geometry course. A mixed-methods design with a convergent parallel approach was adopted to provide a comprehensive understanding of the learning process. Research data were obtained from a questionnaire focusing on students’ experiences during project-based activities and learning outcome scores. The participants consisted of 22 students from a Mathematics Education program during one semester of instruction. The research results showed high student responses toward the lecturer’s presentation, the usefulness of instructional tasks/media, and lecture satisfaction. In contrast, lower scores were observed for the lecturer’s interpersonal approach/friendliness and the interestingness of the material course content. Students reported using efficient strategies supported by visualisation tools, such as GeoGebra, to better understand problem structures. The integration of findings suggests that PjBL provides a learning environment that supports reflective engagement with problem-solving processes in analytical geometry.